Negative urgency and ad-libitum smoking topography. (1st August 2019) - Borges, Allison M.; Leyro, Teresa M.; Rosen, Rachel L.; Zvolensky, Michael J.; Farris, Samantha G.
Highlights: NU (Negative Urgency) may be associated with smoking reinforcement assessed via smoking topography. NU and distress not significantly associated with average-level topography data. NU and distress were associated with puff duration and inter-puff interval. Abstract: Background: Negative urgency (NU), the tendency to act rashly in response to distress, is associated with negative reinforcement smoking expectancies. The study examined whether NU was associated with behavioral smoking reinforcement in the context of self-reported distress. Method: Non-treatment seeking daily smokers (n = 124) completed an ad-libitum smoking trial. Puff topography, including puff volume, duration, velocity, and inter-puff interval, was averaged across the cigarette and evaluated at the puff level. Results: Multilevel models revealed a significant interaction of NU and distress as reported on the Subjective Units of Distress scale over the course of smoking in relation to puff duration and inter-puff interval. There was a significant effect of quadratic time x NU x distress on duration (b=-0.00004, p = 0.04). Smokers lower in NU reporting lower baseline distress evidenced a puff duration that decreased at a faster rate over the course of a cigarette following a quadratic function. Persistently elevated puff durations over the course of a cigarette were observed among smokers with elevated NU, regardless of basal distress. There was also a linear time x NU x distress interaction on inter-puff interval (b=-0.01, p = 0.04). Lower NU smokers, regardless of acute distress, exhibited increasing inter-puff intervals that stabilized over the course of a cigarette. Smokers with elevated NU in the context of low distress also demonstrated linearly increasing inter-puff intervals, while they demonstrated increasing intervals followed by decreasing intervals in the context of higher distress. Discussion: Trait NU in the context of acute distress may contribute to differences in puff topography.